Ajuste de un modelo cinético para el crecimiento de Lactobacillus Acidophilus en la fermentación de sustrato complejo (2017)
This study carried out a microaerofilic fermentation during 96 hours using bacterias Lactobacillus and gender acidophilus, under constant mixing at 150 rpm and a temperature range between 34-37°C. To collect data, a sample was taken every 12 hours, for the sowing and counting by the plate counting technique. The microbial growth curve is obtainer later. From the experimental data collected, 8 unstructured kinetic models were compared whose parameters were estimated from the adjustment of the experimental data through non-linear regressions. The fermentative processes were simulated with the parameters obtained and compared with the experimental data according to the correlation coefficient and the percentage of error of least squares. The models of Haldane and Amrane and Prigent were the ones that best adjusted to the experimental data, with an R2 of 0.977 and 0.982, respectively. These kinetic parameters obtained that describe the growth of the microorganisms involved in the fermentation, allow to predict the performance, yields and behavior in general of the fermentative processes.